2019
DOI: 10.1093/jmcb/mjz006
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule activators of the p53 response

Abstract: Drugging the p53 pathway has been a goal for both academics and pharmaceutical companies since the designation of p53 as the ‘guardian of the genome’. Through growing understanding of p53 biology, we can see multiple routes for activation of both wild-type p53 function and restoration of mutant p53. In this review, we focus on small molecules that activate wild-type p53 and that do so in a non-genotoxic manner. In particular, we will describe potential approaches to targeting proteins that alter p53 stability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 110 publications
1
26
0
Order By: Relevance
“…Pol I inhibitors have been recognized to be a novel strategy to activate the p53 pathway (Ladds & Lain, 2019) and both genetic deletion and pharmacological inhibition of p53 aggravate the development of PAH in animal models (Jacquin et al, 2015;Mizuno et al, 2011). Further supporting our current results, Mouraret et al (2013) have shown that nutlin-3, a small molecule that blocks the p53 degrading activity of the ubiquitin ligase MDM2, exhibits potent therapeutic effects against experimental pulmonary hypertension and suppresses pulmonary arterial remodelling.…”
Section: Cx-5461 Attenuates Inflammatory Cell Infiltration In Pah Lungssupporting
confidence: 82%
“…Pol I inhibitors have been recognized to be a novel strategy to activate the p53 pathway (Ladds & Lain, 2019) and both genetic deletion and pharmacological inhibition of p53 aggravate the development of PAH in animal models (Jacquin et al, 2015;Mizuno et al, 2011). Further supporting our current results, Mouraret et al (2013) have shown that nutlin-3, a small molecule that blocks the p53 degrading activity of the ubiquitin ligase MDM2, exhibits potent therapeutic effects against experimental pulmonary hypertension and suppresses pulmonary arterial remodelling.…”
Section: Cx-5461 Attenuates Inflammatory Cell Infiltration In Pah Lungssupporting
confidence: 82%
“…The first is to target mutp53 directly by restoration of the wild-type tumor-suppressive function of p53 or deprivation of mutp53 through inducing its degradation. The second is to target specific mutp53-binding proteins or critical downstream signaling pathways of mutp53 to inhibit mutp53 GOF activities ( Blandino and Di Agostino, 2018 ; Ladds and Lain, 2019 ; Zhou et al., 2019 ).…”
Section: Therapeutic Strategies To Target Mutp53mentioning
confidence: 99%
“…In the past 20 years, several chemical libraries were developed with the aim of inhibiting MDM2 and p53 interaction and currently only one small molecule, HDM201, has undertaken clinical development for colorectal cancer in combination therapies [24,25] …”
Section: Introductionmentioning
confidence: 99%